Synthesis of porous materials by the modification of coal fly ash and its environmentally friendly use for the removal of heavy metals from wastewater - Hussain, Zawar; Zhang, Hao; Chang, Na; Wang, Haitao (Frontiers in Environmental Science, 2022)
Wastewater is a complex mixture of many pollutants, where the high-risk pollutants are heavy metals (HMs) in industrial wastewater due to their difficult removal. In this study, the waste CFA was used as the main raw material for production of new innovated flocculants porous particles by modification of coal fly ash (CFA) using a multi-step base–acid–base (NaOH–HCl–NaOH) modification method. The morphological structure and elemental composition of the prepared MCFA were analyzed through characterization analysis, i.e., SEM, EDX, FT-IR, BET, XPS, and XRD. Results found that the surface area of the flocculant particles of MCFA was increased from 5.241 to 32.011 m2/g, which increased the adsorption process of HMs (Mn2+, Cu2+, Ni2+, and Pb2+). The maximum removal efficiencies (Re %) of MCFA for Mn2+, Cu2+, Ni2+, and Pb2+ were recorded at 94.26%, 95.88%, 71.04%, and 99.91%, respectively. The Freundlich isotherm model was fitted for the adsorption process, and the maximum adsorption amounts of MCFA for Mn2+, Cu2+, Ni2+, and Pb2+ were 558.9219, 0.4341, 210.9737, and 12.1957 mg/g, respectively. Moreover, the kinetic model indicated that physicochemical adsorption occurred between the adsorbate materials and the adsorbent.